A Basic Right Denied: The Interplay Between Various Factors Contributing to School Dropouts in Pakistan - Abid, Saadia; Ali, Syed Murad; Ali, Inayat (Frontiers in Education, 2021)
Enshrined in different conventions nationally and internationally, education is a fundamental right of every child irrespective of identity and location worldwide. Despite the Universal Declaration of Human Rights (UDHR) 1948 and the United Nations (UN) Convention on the Rights of the Child 1989, education is not accessible and affordable for every child globally due to several entwined factors. Focusing on Pakistan’s Sindh Province, this article identifies the numerous factors that lead to school dropouts and illustrates their interconnectedness. Employing Sen’s Capabilities Approach, we show a correlation between freedom and function, whereby a capability can only be a function if there is an opportunity. We conclude and suggest that since the basic right of education is denied in Pakistan owing to sociocultural, economic, and political factors, there is a need to make necessary efforts at the parental as well as national policy level to address it. We also ask for ethnographically rich studies that should comparatively and thoroughly bring this dropout problem to the center stage for generating a comprehensive understanding so that this basic right is given to every child of this country.